NAVIGATING THE DIGITAL MAZE: INNOVATIVE STRATEGIES AND HURDLES IN ONLINE GRAMMAR INSTRUCTION - Ananda, Jumriah; Nanning, Nanning; Nurhamdah, Nurhamdah; Sardi, Ahmed (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2024)
This study investigates innovative strategies and challenges in online grammar instruction within the English Language Education Department at IAIN Parepare, Indonesia. As digital learning becomes increasingly integrated into higher education, the research focuses on the experiences of 40 students and 5 online grammar instructors. Through a mixed-methods approach, incorporating surveys of all 40 students and in-depth interviews with the 5 tutors, this study investigates the adaptation of traditional grammar teaching methods to digital platforms. Key findings reveal that interactive tools, gamification, and personalized learning paths significantly enhance student engagement and comprehension in online grammar lessons. However, challenges such as varying levels of digital literacy among students, maintaining consistent motivation in virtual environments, and the limitations of asynchronous communication emerge as significant hurdles. The study concludes by proposing a tailored framework for effective online grammar instruction at IAIN Parepare, emphasizing the integration of culturally relevant multimedia resources, collaborative learning activities, and adaptive assessment techniques. These insights contribute to the growing body of knowledge on digital pedagogy in Indonesian higher education and offer practical implications for educators navigating the complexities of online language instruction in similar institutional settings.